Design and Implementation of a React.js-Based Monitoring Dashboard for Tangerang Weather Radar and Server Room Air Conditioning Control - Muhammad Fadil Pradana Andi Alief; Nadila R Muhiddin; Bintoro Puspo Adi; Kadek Ari Sudama (Yayasan Kita Menulis - JoCPES, 2025)
The Tangerang Weather Radar Station plays a critical role in aviation safety, yet its maintenance workflow is currently fragmented. Technicians must monitor radar telemetry and control server room cooling systems using separate, non-integrated platforms. This study addresses this inefficiency by developing a centralized web dashboard based on the React.js and Node.js framework. The system integrates real-time BITE (Built-In Test Equipment) data from the radar and provides remote control for the air conditioning units via an existing IoT infrastructure. Testing results demonstrate that the dashboard accurately renders telemetry parameters (High Voltage Power Supply, Transmitter Power, and VSWR) and executes AC control commands with minimal latency within the local network environment. The responsive design ensures accessibility across desktop and mobile devices, providing a unified